Technological modes of manufacturing medical purpose thermoelectric sensors - Kobylianskyi , R.R.; Lysko, V.V.; Prybyla, A.V.; Konstantynovych, I.A.; Kobylianska, A.K.; Bukharaeva, N.R.; Boychuk, V.V. (Journal of Thermoelectricity, 2023)
The paper presents technological modes of manufacturing thermoelectric heat flow converters. It has been established that the optimal thermoelectric material for a thermopile is low-temperature materials based on Bi2Te3. The efficiency of using such technological modes for the production of thermoelectric micro thermopiles capable of recording laser radiation with an improved conversion coefficient of 1-1.5 orders of magnitude compared to existing measuring transducers has been experimentally confirmed. The specified technological modes significantly simplify and mechanize the method of manufacturing thermoelectric heat flow sensors for medical purposes and microgenerators for powering low-power medical equipment.